923 How Did the Initial Wave Of COVID-19 Affect CEPOD Waiting Times for Vascular Surgery? A Comparative Audit. (12th October 2021) - Wallace, J; Faiz, J; Lowry, D; Williams, A; Davies, C
Abstract: Aim: Many vascular patients present acutely, relying on emergency theatre availability when surgical intervention is required. The prioritisation of the CEPOD operating list is a challenge, and the additional pressures of the COVID-19 pandemic have necessitated changes to established practice. The purpose of this audit was to review the effects of the pandemic on the CEPOD waiting times for vascular patients at the main centre for the South West Wales Vascular Network. Method: The CEPOD waiting times for vascular patients during the initial wave of the COVID-19 pandemic were compared with the same period the previous year. Data was analysed according to booking category and procedure type. Results: 98 emergency vascular procedures were performed during the initial wave of the COVID pandemic, compared to 133 in 2019. In 2019, amputations (major and minor) accounted for 47% of cases, which rose to 53% during the pandemic. Median waiting times for category 1 and 2a operations were significantly shorter in 2020, whilst category 3 waiting times rose. There was no significant difference overall in the proportion of patients operated on within the target timescale, regardless of CEPOD booking category. Conclusions: Managing the impact of COVID-19 required change to established practice. Although fewer procedures were performed, significant logistical challenges were faced. By adjusting the organisation of CEPOD, the most urgent vascular cases were performed quicker during this time. It is important to identify and promote the positive organisational changes that have arisen as a result of COVID-19, and to continue to review procedures as the pandemic progresses.